AS PERCEPÇÕES DE (FUTUROS) PROFESSORES DE LÍNGUA MATERNA SOBRE A LEITURA: AUTOAVALIAÇÃO COMO LEITORES E POSICIONAMENTO ENQUANTO (FUTUROS) DOCENTES - Pereira, Juliana Regiani (2019)
Reading involves reasoning and reflections in the process of comprehension of a text. Its learning has been more studied, throughout the last decades, after research advances in the areas of psycholinguistics, cognitive psychology and neuroscience. Understanding the importance of teaching reading in order to address functional illiteracy issues emerged the interest to research which perceptions (future) mother language teachers have concerning reading and its teaching, during the educational stages after the literacy phase. This survey involved 36 undergraduate students from the 1st grade and 16 undergraduate students from the 4th grade in the Portuguese Major of a public university located in the central-south region of Paraná. We observed, having a questionnaire as our research instrument, each (future) mother language teacher’s profile and one’s self-perception as a reader, yet, we verified their self-assessment as readers; moreover, it was investigated if they use and/ or have knowledge on reading strategies. In addition, the self-assessment they do concerning the teaching practice of reading was also analysed in order to establish a comparison between the 1st and the 4th grade students in relation to the objectives mentioned above. The main results of this research have shown that 31% of 1st grade students consider to be “always” good readers, whereas 56% of the group consider to be “sometimes” good readers. Among 4th grade students, 44% “always” consider themselves as good readers and 50% “sometimes” do. Both beginner and concluding undergraduate students apparently have good reading habits, since, besides reading several genres and in different modes of presentation, 33% of 1st grade participants are “always” used to visit libraries while 56% “sometimes” do. Among 4th grade students, 44% report they “always” go to libraries and 38% “sometimes” do that. In general, we can infer from this investigation that the majority of participants seem to read proficiently, nevertheless a considerable portion of students, mainly concluding ones, claimed not to know what reading strategies are, even having shown their usage in their reading, what makes us think that they do not know about theoretical framework of this or other themes related to reading comprehension. Despite this fact, it is worth considering that a significant majority (95% from the 1st grade and 88% from the 4th grade) comprehends that reading needs to be taught during all the educational stages and not only through the literacy phase, therefore, they evaluate the teaching of reading as one of their responsabilities as (future) mother language teachers.